Large Granular Lymphocytic Leukemia: A Report of Response to Rituximab - Uroosa Ibrahim; Sara Parylo; Shiksha Kedia; Shafinaz Hussein; Jean Paul Atallah (Case Reports in Hematology)
Large granular lymphocytic (LGL) leukemia is a rare form of low grade leukemia characterized by large cytotoxic T cells or natural killer cells on morphological examination. Immunosuppressive therapy is employed as first-line therapy. Treatment options in refractory cases include the anti-CD52 antibody alemtuzumab and purine analogues. We report a rare case that responded to the anti-CD20 monoclonal antibody rituximab. A 77-year-old female presented with complaints of fatigue, fever, and chills of 3 months’ duration. A CBC showed that pancytopenia with an absolute neutrophil count (ANC) was 0. Peripheral blood flow cytometry detected increased number of T cell large granular lymphocytes and T cell receptor rearrangement study detected a clonal T cell population. Bone marrow biopsy showed peripheral T cell lymphoma, most consistent with T-large granulocytic leukemia. The patient was treated with prednisone and oral cyclophosphamide for four months with no response. Thereafter, she received four weekly infusions of rituximab with improvement in her blood counts. A response to rituximab in refractory cases such as ours has been reported and may guide us towards exploring other immune-based therapeutics in this rare disease.